Of Birdhouses and Mosaic Cats: Conquering Fears in the Muddle of Inquiry (LEARNing Landscapes, 2011)
This reflection considers the aspects of classroom focus, instructional practice, and evaluation that impact successful inquiry, as viewed through the author’s experience in an adult art class.Topics considered include varying organization for the appropriate problem type; and creating a classroom supportive of inquiry through encouraging questioning,teaching independence,and using effective formative and self-evaluation.
Keywords: classroom focus; instructional practice; inquiry; evaluation; art; questioning; teaching independence; effectice evaluation; formative evaluation; self-evaluation